Plasma treatment of polyamide fabric surface by hybrid corona-dielectric barrier discharge: Material characterization and dyeing/washing processes - Gasi, Fernando (2020)
In this study, the hybrid corona-dielectric barrier discharge plasma treatment was employed to modify the physical, chemical and morphological characteristics of a half-knitted fabric composed of 92% polyamide 6.6 and 8% elastane (PA). These properties of the fabric were evaluated by the water contact angle, x-ray diffraction, infrared spectroscopy, scanning electron microscopy and atomic force microscopy techniques. In addition, the dyeing and washing processes were also investigated. A significant reduction of the contact angle was observed for plasma-treated PA. Infrared spectroscopy analyses indicated that C-H, N-H, and N-O groups in PA increased after plasma treatment, explaining the improved coloring strength for the plasma-treated samples when dyed with reactive and acid dyes. A better fixation of dye was also observed after the atmospheric plasma treatment. Furthermore, dyeing with a basic and acid dye caused the dyeability increases for the plasma-treated sample compared with the untreated sample.